High power density laser matter interaction - Wang, Weilong. (2008)
High power density laser matter interaction experiments are reported for four target materials (Al, Si, Cu, Au) being irradiated by three different laser energies of 0.2 Joule, 1.0 Joule and 5.0 Joule. This energy range was chosen because it is used in most applications.